The Right Pause - Chauhan, Dinesh (Homœopathic Links, 2013)
Here, illustrating through the case of a carbon remedy, the importance of a pause while understanding a human being through homoeopathic case taking. It is not just a case; it is an experience that changed my whole understanding of the case taking (witnessing) process.
Keywords: Urticaria; Carbo animalis; Case witnessing process; Case taking; Nonverbal language